A coding system to quantify powerful actions in soccer match play: a pilot study. - Murtagh, C.; Naughton, R.; McRobert, A.; O`Boyle, A.; Morgans, R.; Drust, B.; Erskine, R. (Research Quarterly for Exercise and Sport, 2019)
Purpose: The powerful activity profile of elite soccer match play has not been documented appropriately to inform specific maximal power assessment and development criteria. The aims of the current study were to develop a reliable soccer-specific powerful action (SSPA) notational analysis coding system that could be used to compare frequency and durations of powerful actions during elite youth soccer match play. Methods: Sixteen elite male English Premier League (EPL) Academy players (19 ± 1 yrs) were recorded by an individual camera during 16 competitive EPL U18 and U21 games. Video footage was analyzed using performance analysis software and SSPAs were coded according to the following categories: initial acceleration, leading acceleration, sprint, unilateral jump and bilateral jump. Results: The SSPA coding system demonstrated very good inter- and intra-rater reliability (kappa coefficients >= 0.827). Elite youth EPL soccer players undertook significantly more initial (31 ± 9) and leading (37 ± 12) accelerations than sprints (8 ± 3; p = .014, d = 1.7, and p < .001, d = 1.7, respectively) and jumps (6 ± 5; p = .002, d = 1.7 and p < .001, d = 1.7, respectively). Players performed a significantly greater number of initial and leading accelerations with action durations below 1.5 s compared to above 1.5 s (p = .001, d = 1.6, and p = .002, d = 1.4), respectively. Conclusions: Our SSPA coding system provides a reliable observational instrument for quantifying the frequency and duration of powerful actions performed during elite soccer match play. In our sample of elite youth soccer players, horizontal accelerations of short duration (< 1.5 s) from different starting speeds appear the most dominant powerful action in elite youth soccer match play.